Online Learning for First-Generation and Underrepresented Minoritized Students: A Literature Review Using a Model of Student Engagement - Gardner, Krista; Leary, Heather (Online Learning, 2023)
First-generation and underrepresented minoritized(URM) studentsmay have greater challenges in online learning than other students. Communities of support can help these highly motivated students be more engaged and successful in the remote learning environment. In this scoping literature review, we identified fifteen categories of first-generation and URM student challenges in online learning as found in peer-reviewed research of the last ten years. We placed these challenges within the Student Engagement model and found them to be barriers of student engagement. The results of our analysis may help guide practitioners and educators in the continuance or creation of theoretically grounded interventions for student support.